Virtual, augmented and mixed reality : 8th International Conference, VAMR 2016, held as part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings /: 8th International Conference, VAMR 2016, held as part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings. (2016) - Unknown
No abstract available